The Formation of Noble Morals in Madrasah Aliyah Negeri (MAN) in West Java - Novi Rizal Umam; Sutaryat Trimansyah; Ikka Kartika; Yosal Iriantara (UIN Sunan Gunung Djati Bandung, 2021)
This study focuses on the issue of the formation of noble morals in MAN 2 Bandung City and MAN 2 Bandung Regency. This research uses a qualitative approach with a qualitative descriptive method. In this study, it discusses how the management system for the formation of noble morals in educational units, especially in MAN 2 Bandung City and MAN 2 Bandung Regency responds to new challenges in this era of globalization which have resulted in many decreases in the quality of human resources, especially related to embedded moral decadence. in students. Besides, it discusses various environmental influences that affect the implementation of the noble character formation program and various problems that arise from the noble character formation program along with the solutions to its solutions. This research shows that the managerial system for the formation of noble morals in the education unit has implemented management principles through the stages of planning, implementing, monitoring, and evaluating every noble character formation program with various advantages and limited resources. This stage is an effort to reduce the increasing level of moral decadence. The many influences and problems that arise are taken into consideration in formulating various strategies as solutions to these problems.